Upaya Pencegahan Praktik Penipuan Online Melalui Sosialisasi Cyberfraud di Desa Pucangrejo - Laely Nova Yunita; Elina Elmaghfiroh; Fadhilah Rahmawati; Zedny Amiq Elmina; Azharia Sebrina N; Putri Zakiah Dairotur Rohmah; Baginda Revian Ashar; Nur Jannah Salsabila; Laeli Ambar Dwi Cahyani; Moch Maola Nasty Gansehawa (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2024)
Fraud is an act in which a person or group of people creates a false impression so that others believe something that is not true. knowing the many benefits of cyberfraud socialization activities, the KKN MIT 18 Posko 71 UIN Walisongo group conducted a study on the prevention of online fraud or cyberfraud in Pucangrejo village. This research uses descriptive qualitative research methods and students describe the social conditions observed specifically and in depth. The location of this research field has been determined by the scope of the research object